Fluoride and endosulfan together potentiate cytogenetic effects in Swiss albino mice bone marrow cells. (February 2021) - Sharma, Anju; John, Placheril; Bhatnagar, Pradeep
In this study, the cytotoxic potential of fluoride and endosulfan in combination was investigated in Swiss albino mice bone marrow cells using the chromosomal aberration (CA) and micronucleus (MN) test systems. Fluoride (25.1 mg kg −1 body weight [bw] in water) and endosulfan (1.8 mg kg −1 bw by oral intubation) were administered orally alone and in combination (fluoride 25.1 mg kg −1 bw + endosulfan 1.8 mg kg −1 bw) to male Swiss albino mice daily for 30 days. A significant ( p < 0.01) increase in micronuclei (MNs) induction and decreased ratio ( p < 0.01) of polychromatic to normonochromatic erythrocytes (indicators of cytotoxicity) were observed compared with saline controls when animals were given the combination of fluoride and endosulfan. A significant ( p < 0.01) increase in MNs induction and no change in the polychromatic erythrocytes to erythrocyte ratio were also observed when endosulfan was given alone. CAs such as gaps, breaks, fragments, rings, exchanges, and polyploidy were recorded in the bone marrow cells. The mean percent frequency of CAs was increased ( p < 0.01) in all the treated groups compared with the control saline group. In the combination group (F + E), the percent frequencies of CAs were significantly higher (13.875%) compared with those in the individual treatment groups of fluoride (4.375%) and endosulfan (6.25%). The mitotic index was calculated as percentage of dividing cells. A significant ( p < 0.01) decrease in mitotic index was observed in all treated groups compared with controls. In the combination group (F + E), mitotic index was significantly less than ( p < 0.01; 4.1 ± 0.49) the saline control (10.8 ± 0.98). These results indicated that repeated intake of endosulfan through various sources in fluoride affected areas resulted in increased cytotoxic effects. The greater effect in the combination group indicated additive interaction of fluoride and endosulfan in inducing cytotoxicity in Swiss albino mice.